Melon Pinter (Mental Health Online) with the Application and Implementation of Biofeedback Midwifery - Mulazimah; Nur Ahmad Muharram; Entin Srihadi Yanti; Fenny Diyan Marini; Amilia Febrianti (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Background: Mental health problems among pregnant women, postpartum mothers, and women of reproductive age remain underdetected at the community level. Limited literacy, stigma, and access to services hinder early detection. Objective: This community service program aimed to strengthen the capacity of health cadres in early mental health detection using the Melon Pinter application integrated with midwifery biofeedback approaches. Methods: The program consisted of socialization, cadre training, application implementation, simple biofeedback practice, and mentoring. Evaluation used pre–post knowledge tests and observation. Results: The results showed improved knowledge and skills of health cadres in mental health screening and stress management education. Cadres were able to independently use the Melon Pinter application during community health activities. Conclusion: The Melon Pinter program is an effective community service innovation to support promotive and preventive mental health services at the community level